Chicken mixed infection in Kotayk region of the Republic of Armenia - A. R. Hakobyan; O. V. Shcherbakov; V. V. Grigoryan; S. V. Yeribekyan; M. A. Movsisyan; L. H. Grigoryan (Российский паразитологический журнал, 2023)
The purpose of the research is study of chicken parasitic associations in small farms of Kotayk region, and analysis of the determined factors. Materials and methods. Research was conducted in 2021 to 2022 in small poultry farms of Kotayk Marz. Poultry feces samples were examined at the Laboratory of Parasitology of the Research Center of Veterinary Medicine and Veterinary Sanitary Expertise, Armenian National Agrarian University. Totally 210 fecal samples were examined. Eimeria spp. oocysts and nematode eggs were detected by means of method after Darling. The results of the research were processed by statistical methods. Results and discussion. Results of the research have shown that poultry eimeriasis had a wide prevalence in Kotayk Region (52.86%). Three species of Eimeria spp. have been detected: E. acervulina, E. tenella, and E. necatrix. E. acervulina was the most prevalence species (34.29%). The highest intensity of the infection has been registered in Nairi and Kotayk Regions of the region. The above-mentioned species of Eimeria spp. have been occurred both in mono- and poly-infection, with various combinations of the species. E. acervulina + E. tenella combination was the most common. Poultry eimeriasis occurred as a mixed-infection with ascaridiasis, heterakiasis, and capillariasis. The highest extensiveness of the poultry infection has been registered in Kotayk and Hrazdan Regions of the region (65.71% in both cases). Geographical location, as well as natural and climatic conditions of the region promote the prevalence of the mixed infection of poultry.